Self-Directed Learning through Streaming Platforms on Students’ Listening Practices - Wahyu Puspita Sari; Fitriah; Agus Salim (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
In the digital era, streaming platforms have reshaped how students engage with English learning beyond the classroom by providing authentic and easily accessible input. They offer informal learning spaces that foster autonomy and continuous language exposure. This study explores the types of streaming platforms students use, how they practice listening through them, and the reasons behind their preferences. The researchers conducted a qualitative descriptive study involving 50 English major students who completed an online questionnaire and 10 students who participated in semi-structured interviews at a public university in Indonesia. The results reveal that students primarily rely on YouTube, Netflix, and Spotify, while Disney+ and Amazon Prime are less preferred due to subscription barriers. Participants practiced listening in different ways watching English films or series with or without subtitles, replaying specific scenes, listening to music and podcasts while noting new vocabulary, and reflecting on their comprehension. Their reasons for platform choice also varied: YouTube was valued for free access and flexibility, Netflix for authentic dialogue and cultural exposure, and Spotify for convenience during multitasking. These findings suggest that streaming platforms play a dynamic role not only as learning tools but as spaces where students independently regulate strategies, sustain motivation, and build listening proficiency in meaningful and personalized ways.